Language-Mediated Visual Orienting Behavior in Low and High Literates - Huettig, Falk; Singh, Niharika; Mishra, Ramesh K. (Frontiers in Psychology, 2011)
The influence of formal literacy on spoken language-mediated visual orienting was investigated by using a simple look and listen task (cf. Huettig & Altmann, 2005) which resembles every day behavior. In Experiment 1, high and low literates listened to spoken sentences containing a target word (e.g., 'magar', crocodile) while at the same time looking at a visual display of four objects (a phonological competitor of the target word, e.g., 'matar', peas; a semantic competitor, e.g., 'kachuwa', turtle, and two unrelated distractors). In Experiment 2 the semantic competitor was replaced with another unrelated distractor. Both groups of participants shifted their eye gaze to the semantic competitors (Experiment 1). In both experiments high literates shifted their eye gaze towards phonological competitors as soon as phonological information became available and moved their eyes away as soon as the acoustic information mismatched. Low literates in contrast only used phonological information when semantic matches between spoken word and visual referent were impossible (Experiment 2) but in contrast to high literates these phonologically-mediated shifts in eye gaze were not closely time-locked to the speech input. We conclude that in high literates language-mediated shifts in overt attention are co-determined by the type of information in the visual environment, the timing of cascaded processing in the word- and object-recognition systems, and the temporal unfolding of the spoken language. Our findings indicate that low literates exhibit a similar cognitive behavior but instead of participating in a tug-of-war among multiple types of cognitive representations, word-object mapping is achieved primarily at the semantic level. If forced, for instance by a situation in which semantic matches are not present (Experiment 2), low literates may on occasion have to rely on phonological information but do so in a much less proficient manner than their highly literate counterparts.